American Strategy of "Sufficient Presence" in the Middle East - I. V. Ryzhov; M. Yu. Borodina; T. V. Baranova (Vestnik MGIMO-Universiteta, 2020)
Abstract: After D. Trump came to power it started developing a new US Middle East policy, based on the regional threat assessment, such as the unstable political situation in a number of regional countries, radical regimes, terrorism, especially ISIS. In addition, the most important task for the Trump administration was to try to regain lost US influence in the region, which resulted in the so-called "strategy of sufficient presence" and in the support of regional allies, "centers of power" such as Israel.A distinctive feature of D. Trump's policy in the region can be considered a change in rhetoric regarding the Iranian nuclear program up to the introduction of new economic sanctions. Moreover, the American approach to the settlement of the Syrian crisis is connected with the prevention of the growing influence of Iran and Russia in the region.American-Turkish relations also underwent significant changes, which were very tense until 2017. The states managed to find common ground on a number of issues of international politics. However, the situation is still significantly complicated by American support for the Kurds in their quest for autonomy.Trump's ratings at home are falling, and therefore there is a possibility that Trump will lose the upcoming presidential elections to his opponent D. Biden. However, trying to predict the prospects of the US Middle East policy in the event of D. Biden's victory, the authors came to the conclusion that it will not undergo significant changes, except for the nuclear deal with Iran. The key tasks of American foreign policy will remain the fight against terrorism, countering the proliferation of weapons of mass destruction, and the search for likeminded states in the region.